Terapia fotodinâmica com rosa bengala em nanoformulação com alfa-ciclodextrina contra suspensões de Streptococcus mutans - Alexandrino, Francisca Jamila Ricarte (2017)
Considering that dental caries is a biofilm-sugar-dependent disease and that S. mutans is considered the most cariogenic microorganism present in the oral biofilm, photodynamic therapy (PDT) has been proposed to supresscariogenic specie. The aim of this study was to assess the efficacy of PDT using blue light (BL) and the photosensitizer (PS) rose bengal (RB) or RB containing nanoparticulated-α-cyclodextrin (RBNP) against suspensions of S. mutans in two different planktonic suspension models. S. mutans suspensions were divided into groups, as follows: absenceof PS and BL, with BLand without PS, absence ofPS and presence of BL and presence of BL andPS. Four different concentrations of RB and RBNP (0.031, 0.062, 1 and 2 µM) and three energy densities of studied light source (3.35; 6.70 and 10.05 J.cm-2) were tested. Treatments were applied after bacteria being suspended in tryptone soy broth (TSB) or 0.89% NaCl (saline). Aliquots of each studied group was plated in BHI agar and submitted to colony forming units counting (CFU/mL) and the data transformed into logarithmical scale.BL did not cause cell death in the absence of RB or RBNP, regardless of planktonic suspension modeltested. For RB, dark cytotoxicity was not observed in TSB model, while in saline model, this cytotoxicity occurred at a 2μM concentration. For RBNP and TSB model, cell death occurred in the absence of light with2μM concentration, as well as it occurredfor 1 and 2 μM concentrations in saline model. In groups where PDT was applied,for bothRB and TSB models, microbial reduction was found from the concentration 1 µM and 3.35 J.cm-2. For higher both PS concentrations and energy densities,bacterial growth was not observed after treatments. For saline model, microbial reduction occurred from 0.031μM concentration and 10.05 J.cm-2. No bacterial growth was observed in energy densities and concentrations greater than 0.062 μMat 10.05 J.cm-2. In TSB model and RBNP, microbial reduction was detected forboth 0.031μM and 0.062μM concentrations in all tested energy densities.. For saline model, bacterial growth was not observed for all groups where PDT was performed. The model of planktonic cells with saline seems to present lower microbial counts compared to the TSB model. Photodynamic therapy performed with RB or RBNP was effective in reductingmicrobial load in S. mutanssuspensions. The addition of nanoparticles favored the RB antimicrobial effect, however, further studies are needed to investigate the effects of therapy in cariogenic biofilms formedin vitro and in situ. Keywords: Photochemotherapy, Dental Caries, Nanotechnology.